Comparison Study Between Local TSH IRMA Kit (CRRT) and Imported TSH IRMA Kit (Riakey, Korea) - Mondrida, Gina; Triningsih, Triningsih; Purwanti, Kristina Dwi; Sutari, Sutari; Setyowati, Sri; Yulianti S, V.; Lestari, Wening; Ariyanto, Agus; Widayati, Puji (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2019)
Thyroid Stimulating Hormone (TSH) is one of hormones that our body need for growth of brains, bones and other tissues and regulate the metabolism in the body. Normal range of TSH for adult is from 0.3 to 5.5 µIU/ml, whereas for baby ranged from 3 to 18 µIU/ml. An Immunoradiometricassay (IRMA) is one of immunoassay technique using radionuclide as the tracer to detect low quantity of analyte. This technique is suitable for determine TSH levels in human blood serum which has complex matrix and various concentration. The Center for Radioisotope and Radiopharmaceutical Technology (CRRT)-BATAN has developed a reagent of TSH IRMA kit. The aim of this research is to compare between local TSH IRMA kit (CRRT-BATAN) and imported TSH IRMA kit (Riakey, Korea) toward 110 adult samples obtained from PTKMR - BATAN. The results showed 97 samples as true negative, 5 samples as true positive, 1 sample as false negative and 7 samples false positive. The comparison study gave diagnostic sensitivity as much as 83.33 %, diagnostic spesificity as much as 93.27 % and accuracy as much as 92.72 %.